Engineering analysis and numerical study on stability evaluation of seepage slope reinforcement stability of Yunmao expressway - Chengzhong, Wang; Shuangjian, Niu (Frontiers in Materials, 2023)
The landslide disaster of weathered rock slope under seepage action is very common, and the research on its reinforcement and stability is the key of engineering. In this paper, the four grades slope of Yunmao Expressway in China is taken as an example. Based on the engineering monitoring results, the stability of slope reinforcement is studied by numerical simulation. The results of engineering monitoring deformation show that the reinforcement method can effectively guarantee the stability of the slope. The numerical simulation method is used to study the stability of reinforced slope under the influence of hydraulic gradient, anchorage length, anchoring force, and anchorage failure position. The numerical study results show that hydraulic gradient has a great influence on the slip of the sliding surface, and the safety factor decreases with the increase of hydraulic gradient. The greater the anchorage length, the greater the stability of the slope. The safety factor increases with increasing anchorage length. The anchoring force increases and the slope displacement decreases, and the change range is greater than other factors. The influence of anchorage failure on the four grades is that the first-grade is greater than the third-grade, the third-grade is greater than the second-grade, and the second-grade is greater than the fourth-grade.